Accountability as a Boundary condition: Moderating Balanced Scorecard Pathways to School Performance - Abdul Aziz; Wahyudin Rajab; Andi Sari Bunga Untung; Novia Nuraini; Rosni Lubis (JUMPA : Jurnal Manajemen Pendidikan, 2026)
Private vocational schools must perform without full subsidy. This study examines how the four Balanced Scorecard perspectives shape the performance of a private health vocational school, and whether accountability conditions those relationships. It adopts an explanatory quantitative approach within an embedded single-case design. Data were drawn from 38 strategic respondents through a census of the institution's management and core teaching staff. Analysis used Consistent Partial Least Squares (PLSc) in SmartPLS 4.0, with moderation tested through a two-stage approach. The customer perspective emerged as the dominant predictor of organisational performance. The financial and internal-process perspectives contributed significantly but secondarily. The growth-and-learning perspective exerted no direct effect, confirming an investment-lag phenomenon in which human-resource investment does not convert into performance on its own. Accountability proved decisive as a moderator. It acted as a pure moderator that activated the otherwise dormant link between human-resource investment and performance, and as a quasi-moderator that strengthened the gains from customer satisfaction and internal-process quality. Accountability is therefore not a downstream reporting duty but an upstream mechanism that governs the return on institutional investment. The implications for educational management are specific and actionable. School leaders should never fund teacher training or academic facilities in isolation. Every professional-development decision must be bound to explicit post-training performance targets, mandatory knowledge dissemination, and transparent public reporting. Managed this way, accountability converts a school's intellectual capital into a durable competitive advantage rather than a recurring sunk cost. The study offers vocational education managers a clear, evidence-based directive for optimising institutional investment.